Discovery of the Potential Novel Pharmacodynamic Substances From Zhi-Zi-Hou-Po Decoction Based on the Concept of Co-Decoction Reaction and Analysis Strategy - Feng, Xin; Bi, Yuelin; Wang, Jiaqi; Li, Tianyi; Yu, Gengyuan; Zhang, Tonghua; Xu, Haoran; Zhang, Chenning; Sun, Yikun (Frontiers in Pharmacology, 2022)
Background: Zhi-Zi-Hou-Po Decoction (ZZHPD), a classic traditional Chinese medicine (TCM) formula, is clinically used to treat insomnia and depression. The analysis strategy based on the concept of co-decoction of TCM is helpful to analyse the effective substances of TCM formula in depth. Aim of the study: This manuscript intends to take ZZHPD as a model sample to explore the phenomenon of co-decoction of complex formula in the combination of liquid chromatography-mass spectrometry (LC-MS) technology, data analysis, and molecular docking. Materials and methods: In the current research, an innovative LC-MS method has been established to study the active ingredients in ZZHPD, and to identify the ingredients absorbed into the blood and brain tissues of mice. And molecular docking was used to study the binding pattern and affinities of known compounds of the brain tissue toward insomnia related proteins. Results: Based on new processing methods and analysis strategies, 106 chemical components were identified in ZZHPD, including 28 blood components and 18 brain components. Then, by comparing the different compounds in the co-decoction and single decoction, it was surprisingly found that 125 new ingredients were produced during the co-decoction, 2 of which were absorbed into the blood and 1 of which was absorbed into brain tissue. Ultimately, molecular docking studies showed that 18 brain components of ZZHPD had favourable binding conformation and affinity with GABA, serotonin and melatonin receptors. The docking results of GABRA1 with naringenin and hesperidin, HCRTR1 with naringenin-7-O-glucoside, poncirenin and genipin 1-gentiobioside, and luteolin with SLC6A4, GLO1, MAOB and MTNR1A may clarify the mechanism of action of ZZHPD in treating insomnia and depression. Conclusion: Our study may provide new ideas for further exploring the effective substances in ZZHPD.